The Integration of Auto-Education and Itqan Principles in Building Children's Intrinsic Motivation: A Case Study at Firdaus Islamic Course - Nijma, Choirun; Machali , Imam (Al Ulya: Jurnal Pendidikan Islam, 2025)
Early Childhood Education (ECE) in Indonesia faces a critical paradox that the societal demand for premature academic skills often undermines the educational goal of fostering intrinsic motivation, a challenge exacerbated by digital distractions. This study analyzes the conceptual and practical integration of the Montessori principle of Auto-Education and the Islamic work ethic of Itqan in cultivating intrinsic motivation and holistic character at Firdaus Islamic Course (FIC). Using a qualitative case study design, data were collected through source triangulation, comprising in-depth interviews, participatory observation, and document analysis and were analyzed thematically. The findings reveal that the synergy between Auto-Education (the how) and Itqan (the spiritual why) creates an effective hybrid pedagogical model. This integration reframes learning as purposeful 'work' ('amal), demonstrably enhancing children's independence, responsibility, and emotional regulation. Crucially, this impact is amplified by a strong parent-school partnership and is consistently transferred to the home environment. The study concludes that this fusion enriches Self-Determination Theory by introducing a transcendental dimension and successfully cultivates robust intrinsic motivation by framing independence as a meaningful act of worship. It thus offers a potent, culturally-grounded solution to contemporary educational challenges.